Modelling Consumer Adoption of Blockchain-based Halal Traceability System: Integrated Behavioural-Innovation Framework - Ramadhan Razali; Muh. Nashirudin; Zulfikar Zulfikar; Mahdi Mahdi (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The increasing complexity of halal supply chains has intensified transparency challenges, yet limited studies integrate behavioural and innovation theories to explain consumer adoption of blockchain-based halal traceability systems. This study aims to analyze consumer demand and identify key drivers influencing the adoption of blockchain-based halal traceability using an integrated theoretical framework. A mixed-method design was employed, involving a survey of 400 respondents across four Indonesian provinces (Aceh, North Sumatra, DKI Jakarta, and West Java), complemented by in-depth interviews with industry stakeholders and thematic analysis. Quantitative data were analyzed using descriptive and explanatory techniques, while qualitative data provided contextual insights into adoption barriers and opportunities. The findings reveal that perceived transparency, trust enhancement, and relative advantage significantly influence consumers’ intention to adopt blockchain-based systems. However, adoption is constrained by low technological literacy, high implementation costs, and regulatory uncertainty. This study integrates TPB, DOI, and SCTT into a unified adoption model while proposing a validated blockchain-based halal traceability framework that emphasizes the need for regulatory harmonization, technological literacy, and financial support to accelerate digital transformation in the halal ecosystem.